Review: Ethnobotanical Studies in West Kalimantan as Biology Learning Resources - Faturrahman, Mas Akhbar; Wahyuni, Dina; Asyrofi, Harun; Sandra, Klaudia Mareta; Ningsih, Kurnia; Afandi, Afandi; Syamswisna, Syamswisna (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: This research aims to present concise information related to implementing ethnobotanical research in West Kalimantan as a biology learning resource. Methodology: This research is classified as qualitative research with the type of literature review. Each scientific article found during the search process is then analyzed, and the results are presented as tables and graphs. Main Findings: Based on the search, 63 scientific articles implement ethnobotanical research in West Kalimantan as a learning resource in biology subjects. The ethnobotanical research includes using plants as medicine, cosmetics, crafts, dyes, traditional ceremonies, boards, food, wrappers, and toys. The learning resources developed include 13 non-digital and 8 digital learning resources. Novelty/Originality of this study: This research is unique in that it presents literature studies related to the implementation of ethnobotanical research, specifically in West Kalimantan, as a biology learning resource.